A green adsorbent derived from banana peel for highly effective removal of heavy metal ions from water. Issue 51 (9th May 2016) - Li, Yingchun; Liu, Jiang; Yuan, Qunhui; Tang, Hui; Yu, Feng; Lv, Xin
Abstract : A novel carbon foam (CF) was prepared via physically activating banana peel and applied for adsorbing various heavy metal ions including Cu 2+, Pb 2+, Cd 2+ and Cr 6+ in aqueous solution. Abstract : A novel carbon foam (CF) was prepared via physically activating banana peel and applied for adsorbing various heavy metal ions including Cu 2+, Pb 2+, Cd 2+ and Cr 6+ in aqueous solution. The material was characterized by scanning electron microscopy, Fourier transform infrared spectroscopy and Brunauer–Emmett–Teller analysis. The influences of several variables such as pH, contact time, temperature and initial concentration of ions were investigated through batch experiments. The sorption capacities of our proposed CF are remarkably higher than those of similar products (banana peel-based) from other reports. Kinetic and equilibrium studies illustrate that the sorption behavior can be better described by pseudo-second-order kinetic and Langmuir isotherm models. The maximum sorption capacities of Cu 2+, Pb 2+, Cd 2+ and Cr 6+ are estimated to be 49.5, 45.6, 30.7 and 25.2 mg g −1 at an equilibrium time of 5 min. Evaluation of the thermodynamic parameters (Δ G ° < 0, Δ H ° > 0 and Δ S ° > 0) show that the ion sorption onto the CF is an endothermic and spontaneous process. It is noteworthy that the efficiency of the produced material for removing metals can be up to 98% for the contact time of 1 h. The removal efficiency values for 10 kinds of metal ions are 1.3 to 98.6 times higher than those using commercial activated carbon as adsorbent. Among them, the removal efficiency for Cu 2+, Pb 2+, Cd 2+ and Cr 6+ is 7.5, 8.9, 8.7 and 16.6 times higher than that of commercial activated carbon, respectively. The obtained material displays a good application prospect in practical wastewater treatment due to its desirable performance, facile preparation and abundant raw material source with a low price.